Mastering intranets : The Windows 95/Nt Edition - Coleman, Pat.; Dyson, Peter ([S.l.] : Sybex Inc, 1997)
This text presents practical solutions to intranet problems, describing the intranet server and browser software needed to set up an intranet and the Internet standards used in an intranet. The book features a set of case studies describing the intranets used by six major US corporations, and also includes sidebars and interviews with corporate personnel actually involved in setting up corporate intranets. The accompanying CD contains HTML templates for setting up specific intranet sites, such as human resources, technical support, training and sales and marketing departments. Additionally, it includes other utilities for creating and maintaining intranets.